DECARBONIZING THE MARGARINE PRODUCTION PROCESS WITH ROOFTOP PHOTOVOLTAICS AND COGENERATION - Gordić, Dušan; Nikolić, Jelena; Josijević, Mladen; Aleksić, Aleksandar; Vukašinović, Vladimir (Journal on Processing and Energy in Agriculture, 2023)
The paper proposes a methodology for defining the optimal solution for the integrated usage of cogeneration and rooftop photovoltaics. The purpose is to minimize CO2 emissions in industrial plants. The methodology is founded on the integral use of energy audit techniques (analyzing energy and material flows in a production process and the dependence of electricity and heat consumption on a production volume) and mathematical optimization (linear programming). In accordance with the obtained consumption profiles, technical limitations and legal regulations, the potential for installing rooftop photovoltaic panels at appropriate locations and the implementation of appropriate cogeneration technologies were analysed. The proposed methodology was tested on a local margarine production facility. The integrated application of cogeneration (gas engines) and photovoltaics can reduce the current CO2 emission by 56% if PV panels are installed on the entire accessible rooftop surface, i.e. up to 44.5% if 150 kW PV panels are installed as the new national regulation proposes.
Keywords: food industry; decarbonization; PV panels; cogeneration